Pengembangan Media Pembelajaran Microsite Berbasis Pendekatan Deep Learning untuk Meningkatkan Hasil Belajar Matematika Siswa Kelas VIII SMP Negeri 4 Semanding - Shofiyyatul Azkiya; Yuliastuti, Rita (Media Pendidikan Matematika, 2026)
This study aimed to develop a deep learning-oriented microsite learning media that is valid, practical, and effective in improving mathematics learning outcomes on the topic of cubes and cuboids for eighth-grade students at SMP Negeri 4 Semanding. The study employed a Research and Development (R&D) approach using the ADDIE model, which consists of Analysis, Design, Development, Implementation, and Evaluation stages. The trial subjects consisted of 29 eighth-grade students selected through purposive sampling. Data were collected through observation, interviews, learning achievement tests, student response questionnaires, and documentation. The research instruments included material expert validation sheets, media expert validation sheets, pre-test and post-test instruments, and student response questionnaires. Data were analyzed using percentage techniques to determine the validity and practicality of the media, while effectiveness was measured using the N-Gain test. The results showed that the microsite learning media met the criteria of being highly valid, with material expert validation scores of 93% and 96%, and media expert validation scores of 80% and 93%. The practicality level reached 100% based on student responses. Furthermore, the average pre-test score of 37.76 increased to 89.83 in the post-test, with an average N-Gain score of 0.90 categorized as high. A total of 27 students achieved a high N-Gain category, while 2 students achieved a moderate category. These findings indicate that the developed microsite learning media is valid, practical, and potentially effective for supporting mathematics learning on cubes and cuboids.